Docetaxel induced subacute interstitial lung disease in a patient with prostate cancer - Sanghai, Rishav; Ghosh, Shantanu; Saraf, Saiyam; Mittal, Stuti (International Journal of Research in Medical Sciences, 2022)
Interstitial lung disease (ILD) is a collective term for a group of disorders that result in inflammation and scarring of the lung interstitium. Although majority of the cases of ILD are idiopathic, some of the etiologies can range from viral infections; connective tissue disorders or drug injury. Docetaxel is an anticancer agent of taxoid family that can rarely cause pulmonary toxicity. It can be occasionally used for the management of advanced prostate cancer. The adverse effects of the medication are mediated by type I and type IV hypersensitivity reactions. Here, we reported a case of 68-year-old man with advanced prostate cancer who completed six cycles of chemotherapy with docetaxel and presented with shortness of breath, low-grade fever and cough two weeks after completion of scheduled regimen. Clinical examination revealed diffuse wheeze and decreased air entryon auscultation, oxygen desaturation and an ulcerative lesion on the left forearm. All his routine serum, sputum and autoimmune profile were inconclusive. The inflammatory markers (CRP, ESR) were raised but procalcitonin was in normal range. Pulmonary function tests were indicative of restrictive lung disease. Digital chest X-ray revealed diffuse opacification with prominent bronchovascular markings and HRCT of thorax reported bilateral scattered honeycomb appearance, subpleural opacities, centrilobular nodules with air trapping. Docetaxel induced interstitial lung disease (DILD) was diagnosed and the patient was advised with high dose systemic and inhalational steroids along with external oxygen support. Rapid clinical improvement was seen and the patient was eventually discharged with tapering doses of oral steroids, physiotherapy and close follow-up.